PENGARUH TEKNIK MARMET TERHADAP KELANCARAN ASI PADA IBU MENYUSUI - Andi Kasrida Dahlan (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Background: The marmet technique is removing the milk manually and assisting the milk exclusion reflex (Milk Ejection Reflex). Objective: Marmet technique influence to fluid breastfeeding in breastfeeding mothers.Method: design in this research is quasi experiment, population in this research are all postpartum gave birth with a normal gestational age with normal birth weight. Sampling using total sampling, with 24 samples, divided into 2 groups, 12 intervention groups and 12 control groups. Data collection using observation sheet and checklist. The data collected was then processed and analyzed using computer program of microsoft excel and statistic program (SPSS) version 20 with data bivariat analysis using chi-square analysis presented in table 2x2 form.Result: No effect of Marmet technique on breastfeeding in breastfeeding mothers before treatment, (ρ- Value = ,640 > 0,05), There is Marmet technique influence to fluid activity of breastfeeding mother after treatment (ρ-Value = 0,027 < 0,05).Conclusion: There is no effect of Marmet technique on breastfeeding in breastfeeding mothers before treatment is given and Marmet technique exists on the smoothness of breastfeeding in breastfeeding mothers after being given treatment. Keywords : PostPartum, Marmet Technique, Smoothness of Breast Milk